Retraction: Ni2[LnCl6] (Ln = EuII, CeII, GdII): the first LnII compounds stabilized in a pure inorganic lattice. Issue 87 (18th October 2019) - Baldo, Bianca; Rubio, Francisco; Flores, Erwin; Vega, Andres; Audebrand, Nathalie; Venegas-Yazigi, Diego; Paredes-García, Verónica
Abstract : Retraction of 'Ni2 [LnCl6 ] (Ln = Eu II, Ce II, Gd II ): the first Ln II compounds stabilized in a pure inorganic lattice' by Bianca Baldo et al., Chem. Commun., 2018, 54, 7531–7534.